Dental maturity as an indicator of chronological age: radiographic assessment of dental age in a brazilian population - Lucio Mitsuo Kurita; Alynne Vieira Menezes; Marcia Spinelli Casanova; Francisco Haiter-Neto (University of São Paulo, 2007)
OBJECTIVE: The purpose of this investigation was to evaluate the applicability of the methods proposed by Nolla and by Nicodemo and colleagues for assessing dental age and its correlation to chronological age. METHODS: Panoramic radiographs of 360 patients from the city of Fortaleza (CE, Brazil) aged 7-15 years were used to assess the associations between dental and chronological age. Data were submitted to statistical analysis using the BioEstat 2.0 (2000) software. Student-Neuman-Keuls test was performed and Pearson's correlation coefficients were calculated at 5% significance level. RESULTS: When the Nolla method was applied, the mean difference between true and estimated age for males and females was underestimated. The use of the method proposed by Nicodemo and colleagues also resulted in underestimation, although it was more evident in male subjects. The correlation coefficients between chronological age and estimated dental age were high, with mean values ranging between 0.87 and 0.91 for males and between 0.84 and 0.93 for females. CONCLUSION: Although both methods proved to be reliable in estimating age, the use of correction factors is recommended.